2016
DOI: 10.1001/jamafacial.2015.1854
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Nasal Valve Obstruction After Functional and Aesthetic-Functional Rhinoplasty

Abstract: INTRODUCTION Nasal valve insufficiency is distinct from other anatomic causes of nasal obstruction. Functional rhinoplasty refers to the collective techniques used to reconstruct the lateral nasal wall, typically achieved with the use of spreader and alar grafts. Patients undergoing functional rhinoplasty can also have aesthetic desires and goals achievable with combined aesthetic-functional rhinoplasty. OBJECTIVE To evaluate the improvement in nasal obstruction symptoms after cartilage graft reconstruction in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 28 publications
(33 reference statements)
1
25
0
1
Order By: Relevance
“…Compared to previously published studies that looked at NOSE score trends over time, our study data appear to be externally consistent. Like Yeung et al and Fuller et al, we found that NOSE scores improve at the earliest time point (1–3 months) and remain improved at the later follow‐up time point (≥10 months.) In our review comparing preoperative and postoperative NOSE scores at three postoperative time intervals (early, middle, and late) we found significant and durable improvement in nasal obstructive severity scores reported as early as the 1‐ to 3‐month time interval, on average.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Compared to previously published studies that looked at NOSE score trends over time, our study data appear to be externally consistent. Like Yeung et al and Fuller et al, we found that NOSE scores improve at the earliest time point (1–3 months) and remain improved at the later follow‐up time point (≥10 months.) In our review comparing preoperative and postoperative NOSE scores at three postoperative time intervals (early, middle, and late) we found significant and durable improvement in nasal obstructive severity scores reported as early as the 1‐ to 3‐month time interval, on average.…”
Section: Discussionsupporting
confidence: 84%
“…However, the ideal follow‐up duration after functional septorhinoplasty has not yet been determined. Previous literature utilizing NOSE scores report variable follow‐up, ranging from 1 month to 4 years …”
Section: Introductionmentioning
confidence: 99%
“…To address this issue, Stewart et al recently have developed and validated the Nasal Obstruction Symptom Evaluation (NOSE) scale, a disease‐specific QOL instrument designed to determine the presence of nasal obstruction . Since then, several studies have compared pre‐ vs. postoperative NOSE scores to assess QOL associated with nasal obstruction …”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, this approach has a reported surgical failure rate to relieve NAO symptoms as high as 25% to 53%, and multiple studies have demonstrated poor correlation between patient‐reported symptoms and objective findings . Failures following surgical correction of deformities involving the inferior nasal corridor oftentimes reveal a previously undiagnosed nasal valve compromise (NVC) that remains unresolved, or incompletely resolved, by otherwise successful correction of targeted anatomic NAO …”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7] Failures following surgical correction of deformities involving the inferior nasal corridor oftentimes reveal a previously undiagnosed nasal valve compromise (NVC) that remains unresolved, or incompletely resolved, by otherwise successful correction of targeted anatomic NAO. [8][9][10] Numerous surgical procedures exist to address NVC beyond the inferior nasal corridor, including spreader grafts, spreader flaps, butterfly grafts, flaring and spanning sutures, batten grafts, and others. Spreader grafts popularized by Sheen 11 can be used unilaterally, bilaterally, asymmetrically, or in combination with flaring 12 and/or spanning sutures.…”
Section: Introductionmentioning
confidence: 99%